The Meaning of Implementation of Pancasila Economic Education for the People of Kota Probolinggo - Dian Fatma Supriyanti; Wahjoedi; Nasikh (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This research is motivated by phenomena that occur in society where economics is taught and developed in a capitalist economics society that is not following the ideology of the Pancasila nation. Pancasila, which is a moral bulwark for the nation's successors, seems to have been narrowed down to democratic education but lacks moral education. The existing development in Indonesia, which should displace existing poverty, actually displaces the poor. This study uses a qualitative approach to the type of phenomenological research. This research was conducted in Dusun Mantong, Kelurahan Sumbertaman, Kota Probolinggo. The selection of informants carried out in the study was carried out by various criteria using the purposive sampling technique. Data collection techniques used are interviews, observation, and documentation techniques. The results of this study are that most people have implemented economic education that is following the values ​​of Pancasila well. This is evidenced by looking at the economic behavior of children following the values ​​of Pancasila, one example is that children behave honestly in every economic activity. The purpose of this study is that human resources in the family behave economically with insight and based on the values ​​of Pancasila.